Survey on visual acuity among intra-city commercial vehicle drivers in Ibadan, southwestern Nigeria - Magbagbeola David Dairo; Ugochukwu Patricia Okechukwu-Nwankpa; Romanus Nwankpa (AOSIS, 2019)
Driving is recognized to be a visually intensive task and accordingly legal minimum standard of vision required for all motorists is stipulated. This study was carried out to find out how many commercial drivers in Ibadan North L.G.A met minimum legal requirement for driving in Nigeria. A cross sectional descriptive study was conducted among 340 commercial vehicle drivers selected by multistage sampling from eight transport stations (motor parks) in the city. Visual impairment was defined as vision acuity (VA) in both eyes which is below 3/18 but above 3/60 (VA <6/18≥3/60) and was assessed with the Snellen's chart. All participants have valid driving licenses. One sixth [52, (15.3%)] have visual acuity below 6/9 and 18 (5.3%) have visual impairment (VA <6/18≥3/60). More of those drivers aged 40 years and more had visual impairment compared to the younger drivers (P<0.05). These findings suggest that regulatory standards for licensing drivers are being circumvented by some of the drivers. Mechanisms for ensuring compliance to the regulatory standards especially visual acuity is therefore recommended.